Análisis y control contable de la empresa rectificadora Jiménez S.A. RECJIMSA, de la ciudad de Machala para la elaboración de un manual de control interno contable - Jaramillo Pineda, Diana Carolina (2015)
The purpose of this study is to determine how it has affected the non-existence of a manual of accounting and financial procedures in the company grinding Jimenez for the execution of the processes of registration and control of transactions. For which an analysis accounting of the company in order to identify deficiencies in the accounting system, and thus to establish registration procedures and controls that enable management financial, design a chart of accounts enabling the correct registration and control of the activities, developing processes, analysis of financial statements for decision making, and implement rules, functions and governance policies for the compliance of the accounting procedures. The methodology to be followed was based on the application of techniques such as: observation of documents and the accounting structure of the entity; We also proceeded to interview the personal accountant of the cooperative in order to meet the different situations that are affected the accounting process, finally applied the technique of the survey addressed to professionals in accounting in order to meet the criteria of professionals in accounting, for in this way establish the guidelines for the development of a manual of accounting procedures. Once the research proceeded to develop a manual of accounting procedures, with the aim of achieving the optimization of the accounting management and the generation of useful and reliable financial statements for decision making.